2002
DOI: 10.1901/jaba.2002.35-283
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Therapist Attention on Self‐injury During a Tangible Condition

Abstract: This study investigated the effects of therapist attention on the self-injurious behavior (SIB) of a 6-year-old girl with developmental disabilities. After results of a functional analysis indicated that SIB was maintained by attention and tangible reinforcement, tangible conditions with and without contingent verbal attention were compared. Results suggested that the inclusion of verbal attention in a tangible condition may confound functional analysis outcomes for behavior that is maintained by attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 8 publications
(8 reference statements)
0
13
0
1
Order By: Relevance
“…Other analyses have examined change between nothing and access to an item. For example, in the tangible condition described by Moore, Mueller, Dubard, Roberts, and Sterling-Turner (2002), preferred items were given, removed, and returned at various times, arranging transitions in both directions. The current analysis differs in that transitions in both directions were programmed independent of responding, whereas more commonly, the transitions analogous to the termination transition are programmed contingent on the passage of time and the transitions analogous to the initiation transitions occur only contingent on the target behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Other analyses have examined change between nothing and access to an item. For example, in the tangible condition described by Moore, Mueller, Dubard, Roberts, and Sterling-Turner (2002), preferred items were given, removed, and returned at various times, arranging transitions in both directions. The current analysis differs in that transitions in both directions were programmed independent of responding, whereas more commonly, the transitions analogous to the termination transition are programmed contingent on the passage of time and the transitions analogous to the initiation transitions occur only contingent on the target behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Moore et al (2002) demonstrated the need to evaluate the potential confound of verbal attention during a tangible condition of a functional analysis. They compared the effects of a tangible condition with and without verbal attention with a 6-year-old girl who engaged in self-injurious behavior.…”
mentioning
confidence: 99%
“…Além disso, atenção verbal (e.g., "Você quer o doce?") liberada simultaneamente com um item tangível contingente ao comportamento-problema pode confundir os resultados da análise funcional 55 . Pacientes podem estar usando equipamentos de proteção (e.g., capacete com proteção na face) para prevenir os danos físicos da emissão de autolesivos.…”
Section: Conclusãounclassified